The Role of Flexible Workspaces in Enhancing Organizational Performance: a Systematic Review - Tuti Lisnawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The COVID-19 pandemic accelerated the adoption of flexible work arrangements (FWAs), prompting a paradigm shift in the traditional work model. This study aims to systematically review the literature on the impact of FWAs and organizational culture on work productivity. A systematic literature review was conducted using a rigorous methodology, including database searches, screening, data extraction, and thematic analysis. The search focused on peer-reviewed articles published in reputable academic journals. The findings from the literature review indicate that FWAs and organizational culture have a significant impact on work productivity. FWAs can enhance work-life balance, job satisfaction, and employee motivation, leading to increased productivity. However, challenges such as social isolation, decreased collaboration, and difficulty in maintaining work-life boundaries may arise. Organizational culture plays a crucial role in shaping employee behaviour and performance. A positive organizational culture characterized by trust, respect, and open communication can foster employee engagement and productivity. However, negative organizational cultures can hinder employee performance and job satisfaction. This systematic literature review highlights the complex interplay between FWAs and organizational culture in influencing work productivity. Organizations should strive to create a positive organizational culture that supports employee well-being, provides opportunities for professional development, and facilitates effective collaboration. By carefully designing and implementing FWAs, organizations can harness the benefits of flexibility while mitigating potential challenges. Further research is needed to explore the long-term impact of FWAs and organizational culture on employee productivity and organizational performance.